Prescription patterns of P2Y12 inhibitors following revascularization in the United States: 2013-2018 - Arun Kumar; Pamela L. Lutsey; Wendy L. St. Peter; Jon C. Schommer; Jeremy R. Van't Hof; Abhijeet Rajpurohit; Joel F. Farley (Wiley, 2023)
Abstract P2Y12 inhibitors (i.e., clopidogrel, prasugrel, or ticagrelor) are effective at reducing adverse cardiovascular outcomes post‐revascularization in coronary artery disease (CAD). However, the choice of a specific P2Y12 inhibitor may vary according to the patient's characteristics, and trends in the use of different P2Y12 inhibitors are not well studied in real‐world settings. The objective of this study is to determine trends in the prescription patterns of P2Y12 inhibitors in patients with CAD. We studied 137,073 patients with CAD cross‐sectionally using the IBM MarketScan database (2013-2018). Patients with CAD prescribed P2Y12 inhibitors within 14 days of index revascularization were included to compare the utilization of P2Y12 inhibitors based on age and clinical characteristics. There were differences in prescription patterns by age. Among patients aged less than or equal to 65 years (N = 92,734), a continuously increased utilization of ticagrelor was observed from 13.7% to 45.6% replacing clopidogrel as the most prescribed medication by 2018. Similarly, ticagrelor was the choice of drug among patients undergoing percutaneous coronary intervention. Among the patients at high bleeding risk, clopidogrel remained the most prescribed medication with use in 50.6% of patients in 2018 in patients aged less than or equal to 65 years. Contrarily, among the older adults with age 65 or above (N = 44,339), although ticagrelor use increased with time, clopidogrel remained the most utilized drug and was used by 66.2% of patients in 2018. Additionally, clopidogrel was the preferred medication among patients with stroke history. With the increasing use of ticagrelor in real‐world practice, further research is needed to observe its impact on cardiovascular outcomes.